Clinical use of hyaluronic acid in andrology: A review. (2nd August 2021) - Zucchi, Alessandro; Scroppo, Fabrizio Ildefonso; Capogrosso, Paolo; Salonia, Andrea; Duante, Jacopo; Bini, Vittorio; Liguori, Giovanni; Bartoletti, Riccardo
Abstract: Background: Hyaluronic acid is a glycosaminoglycan widely used in the fields of orthopedics, ophthalmology, and aesthetic medicine due to its significant ability to reduce the synthesis of pro‐inflammatory proteins and its activity against oxidative stress, a feature of many degenerative illnesses. Objectives: The objective of the present review is to provide a comprehensive narrative review of the most recent literature on the use of hyaluronic acid in andrology in order to facilitate the use of this therapeutic device in the common clinical practice of many physicians. Specific conditions covered in the review are Peyronie's disease, premature ejaculation, and penile enlargement. Materials and methods: A broad and comprehensive literature search included Medline, EMBASE, and the Cochrane Libraries, with no time restriction up to December 2020 and restricted to English language publications. Unpublished studies were not included. The study was registered as "The role of hyaluronic acid in andrology: A systematic review and meta‐analysis" in PROSPERO with the ID CRD42021223416. Discussion and conclusion: Hyaluronic acid is a valid choice for the treatment of Peyronie's disease in terms of the resolution of the acute phase of the disease and of contributing to stabilizing the disease as a bridge to potential surgery. Data, furthermore, suggest that hyaluronic acid is frequently associated with an overall clinical improvement, allowing the patient to resume normal sexual activity. With regard to premature ejaculation, data suggests hyaluronic acid‐based treatments were effective in prolonging intra‐vaginal ejaculation time. Furthermore, hyaluronic acid was found to be safe and well‐tolerated, with main adverse events limited to local discomfort, ecchymosis, papule formation, and glans numbness, all of which were reported to resolve spontaneously. Last, with regard to penile enlargement, the overall perception of experts is that hyaluronic acid may be an extremely well‐tolerated compound with potential for application in specific areas of male sexual health that are often neglected as compared to more common, and relatively simpler to treat, conditions.